Identification of a transposon-like insertion in a Glu-1 allele of wheat. - Harberd, N; Flavell, R; Thompson, R (Springer-Verlag, 1987)
The Glu-1 locus, present on the long arms of the group 1 chromosomes of wheat, codes for a group of storage protein polypeptides termed high molecular weight (HMW) subunits of glutenin. Hexaploid wheat varieties carry a 'silent' Glu-1y allele on chromosome 1A, no polypeptide being attributable to this locus. When two such alleles from different varieties were compared, one was found to contain an 8 kb insertion of DNA, termed Wis-2, interrupting the coding sequence. The insertion site is flanked by a 5 bp duplication. The two ends of Wis-2 contain similar sequences over 500 bp long and its termini contain almost the same short sequences but in opposite orientation. These terminal sequences are related to those of several 'retroposon'-type transposable elements found in other organisms.